2002
DOI: 10.1074/jbc.m202273200
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Control of the Isoalloxazine Environment in the Two-electron Reduced States of Yeast Glutathione Reductase

Abstract: The resonance Raman spectra of the oxidized and two-electron reduced forms of yeast glutathione reductase are reported. The spectra of the oxidized enzyme indicate a low electron density for the isoalloxazine ring. As far as the two-electron reduced species are concerned, the spectral comparison of the NADPH-reduced enzyme with the glutathione-or dithiothreitol-reduced enzyme shows significant frequency differences for the flavin bands II, III, and VII. The shift of band VII was correlated with a change in ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Structures from subgroups that are lacking the lysine residue have a water molecule overlapping the ɛ-amino group of the lysine, as shown in Figure 5. This lysine or water molecule may play a role in stabilizing the reduced flavin intermediate by hydrogen bonding [31]. In support of this notion, a similar mechanism involving an active-site water molecule has been proposed in adrenodoxin reductase [32].…”
Section: Resultsmentioning
confidence: 93%
“…Structures from subgroups that are lacking the lysine residue have a water molecule overlapping the ɛ-amino group of the lysine, as shown in Figure 5. This lysine or water molecule may play a role in stabilizing the reduced flavin intermediate by hydrogen bonding [31]. In support of this notion, a similar mechanism involving an active-site water molecule has been proposed in adrenodoxin reductase [32].…”
Section: Resultsmentioning
confidence: 93%
“…The vibrational assignment of the oxidized flavin has been well-established, and the customary numbering of Raman bands is given in the upper part of the figure. Band I of the oxidized flavin, which is attributed to an almost pure ring I mode and is generally observed around 1630 cm -1 , ,, appeared at a distinctly lower frequency for (6−4) photolyase (1621 cm -1 in both H 2 O and D 2 O). All bands above 1340 cm -1 are H 2 O/D 2 O insensitive, meaning that they arise from rings I and/or II, since neither ring has exchangeable protons.…”
Section: Resultsmentioning
confidence: 95%
“…10 -12 Physicochemical analysis has shown that the major composition of JB is oxygen-deficient ZnO containing a significant number of nanoparticles of 10-25 nm size. 13 The cell line used, S. cerevisiae, has previously been studied using Raman spectroscopy by Picaud and Desbois, 14 who studied alcoholic fermentation in S. cerevisiae as a function of hydrostatic pressure. Singh et al 15 studied the stress response of S. cerevisiae (i.e.…”
Section: Introductionmentioning
confidence: 99%